Domestic violence against women in India: A systematic review of a decade of quantitative studies - Kalokhe, Ameeta (Glob Public Health, 2016)
Domestic violence (DV) is prevalent among women in India and has been associated with poor mental and physical health. We performed a systematic review of 137 quantitative studies published in the prior decade that directly evaluated the DV experiences of Indian women to summarise the breadth of recent work and identify gaps in the literature. Among studies surveying at least two forms of abuse, a median 41% of women reported experiencing DV during their lifetime and 30% in the past year. We noted substantial inter-study variance in DV prevalence estimates, attributable in part to different study populations and settings, but also to a lack of standardisation, validation, and cultural adaptation of DV survey instruments. There was paucity of studies evaluating the DV experiences of women over age 50, residing in live-in relationships, same-sex relationships, tribal villages, and of women from the northern regions of India. Additionally, our review highlighted a gap in research evaluating the impact of DV on physical health. We conclude with a research agenda calling for additional qualitative and longitudinal quantitative studies to explore the DV correlates proposed by this quantitative literature to inform the development of a culturally tailored DV scale and prevention strategies.